Citizens' acceptance of sustainable public construction in their municipality - Ellen Sterk; Morten Endrikat; Dmytro Katerusha (Philipps-University Marburg, School of Business and Economics, 2023)
Green public procurement of construction activities has the potential to significantly reduce a municipality's environmental footprint. Moreover, it is likely to positively affect its citizens' implementation of green building practices. However, the degree of citizens' acceptance of sustainable building by their municipality remains unstudied as do the factors that are of influence in this regard. Through a survey in four German municipalities, this study investigates public acceptance of sustainable public construction in its two dimensions: attitude and action. The findings consistently reveal positive attitudes, which are driven by trust in the municipality and the perception of personal as well as social benefits. As anticipated, costs negatively impact citizens' attitudes. Despite these generally positive attitudes, only specific segments of the public demonstrate a willingness to actively support sustainable public construction. Whether or not citizens are willing to engage is influenced by the form of action, age, as well as their interest in and knowledge of sustainability and construction. In contrast, additional costs and the type of building in question do not appear to have an effect. The use of the default effect is demonstrated to have the potential to enhance the behavioral dimension of public acceptance. Implications for government institutions and suggestions for further research are provided.
Keywords: 330